2012
DOI: 10.1111/j.1467-8683.2012.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Board Composition: The Role of Nomination Committees

Abstract: Manuscript Type: Empirical Research Question/Issue: The global financial crisis in 2008 has generated increasing recognition of the importance of board diversity reflected amidst the capabilities and skills of directors on a board. As the primary institutional mechanism designed to strengthen the director selection process, nomination committees (NCs) occupy centre stage of this discussion. However, there is a dearth of studies which focus either specifically on NCs or on diversity as a board composition outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 97 publications
(144 reference statements)
2
95
0
2
Order By: Relevance
“…High levels of transparency create higher pressure on companies to comply, and ultimately to cope with any kind of biases in selection or treatment. For instance, nomination committees influence gender diversity in boards (Kaczmarek, Kimino, & Pye, 2012). The presence of women can have direct effects on corporate reputation (Bernardi, Bosco, & Columb, 2009;De Anca & Gabaldon, 2014b) as well as CSR actions (Bear, Rahman, & Post, 2010;Boulouta, 2013), and corporate sustainability (Galbreath, 2011).…”
Section: Demand Sidementioning
confidence: 99%
“…High levels of transparency create higher pressure on companies to comply, and ultimately to cope with any kind of biases in selection or treatment. For instance, nomination committees influence gender diversity in boards (Kaczmarek, Kimino, & Pye, 2012). The presence of women can have direct effects on corporate reputation (Bernardi, Bosco, & Columb, 2009;De Anca & Gabaldon, 2014b) as well as CSR actions (Bear, Rahman, & Post, 2010;Boulouta, 2013), and corporate sustainability (Galbreath, 2011).…”
Section: Demand Sidementioning
confidence: 99%
“…However, studies have shown that there are some positive effects of the crisis for diversity. James (2014) found that providing work-life balance mechanisms for employees, such as child care, is consistent with improvements in firm performance; Kaczmarek et al (2012) noted that in the business context there is value in diversity; and Briskin (2014) suggested that that gender equality can be a way out of the quagmire of austerity for unions. An example of positive outcomes is the tendency of some boards to increase diversity among board members during financially difficult times; 'one is a token, two is a presence, three is a voice' (Gyapong et al, 2016: 373).…”
Section: Positive Aspects For Diversity In the Context Of The Economimentioning
confidence: 99%
“…For example, unemployment filing requirements for women and youth were relaxed in some countries, such as Finland, France, Portugal, and Latvia (Leschke, 2012). James (2014) found that providing work-life balance mechanisms for employees, such as child care, is consistent with improvements in firm performance; Kaczmarek et al (2012) noted that in the business context there is value in diversity; and Briskin (2014) suggested that that gender equality can be a way out of the quagmire of austerity for unions. Diversity is seen by many as good for business, although it is still a hard sell (James, 2014).…”
Section: Positive Aspects For Diversity In the Context Of The Economimentioning
confidence: 99%
“…For instance, we do not know enough about the influence of structural board components, such as the number and independence of directors, as well as board committee structure, on the CFO. Despite first attempts to gain a better understanding of board selection committees (Kaczmarek, Kimino, & Pye, ), our knowledge on their importance for CFO selection is still limited. How do nomination committees, especially directors with financial expertise, define which CFO candidate shows the best fit with their firm and assess her potential to become a valuable member of its top team?…”
Section: A Future Research Agenda On Board Governance Of the Cfomentioning
confidence: 99%